2012
DOI: 10.1242/dev.081448
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role for a conserved motif adjacent to the homeodomain of Hox10 proteins

Abstract: SUMMARYDevelopment of the vertebrate axial skeleton requires the concerted activity of several Hox genes. Among them, Hox genes belonging to the paralog group 10 are essential for the formation of the lumbar region of the vertebral column, owing to their capacity to block rib formation. In this work, we explored the basis for the rib-repressing activity of Hox10 proteins. Because genetic experiments in mice demonstrated that Hox10 proteins are strongly redundant in this function, we first searched for common m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 44 publications
(71 reference statements)
0
23
0
Order By: Relevance
“…Interestingly, alternatively spliced mRNAs are also produced from the Hoxa10 locus, and encode a predicted protein that is essentially the homeodomain without any significant N-terminal attached to it (Benson et al, 1995). The role of such a molecule is still unclear, as functional analysis in transgenic mice indicate that it is not able to activate the typical Hoxa10 patterning programme in the axial skeleton or interfere with it (Guerreiro et al, 2012). Hoxb3 and Hoxa5 also produce different mRNA isoforms through a combination of alternative splicing and alternative promoter usage; interestingly, the resulting isoforms are expressed in different domains during embryonic development (Chan et al, 2010;Coulombe et al, 2010;Sham et al, 1992), once again suggesting that the resulting isoforms might carry out specific functions.…”
Section: Review Development 140 (19) Review Development 140 (19)mentioning
confidence: 99%
“…Interestingly, alternatively spliced mRNAs are also produced from the Hoxa10 locus, and encode a predicted protein that is essentially the homeodomain without any significant N-terminal attached to it (Benson et al, 1995). The role of such a molecule is still unclear, as functional analysis in transgenic mice indicate that it is not able to activate the typical Hoxa10 patterning programme in the axial skeleton or interfere with it (Guerreiro et al, 2012). Hoxb3 and Hoxa5 also produce different mRNA isoforms through a combination of alternative splicing and alternative promoter usage; interestingly, the resulting isoforms are expressed in different domains during embryonic development (Chan et al, 2010;Coulombe et al, 2010;Sham et al, 1992), once again suggesting that the resulting isoforms might carry out specific functions.…”
Section: Review Development 140 (19) Review Development 140 (19)mentioning
confidence: 99%
“…Combining gene expression data and transcription factor activity prediction based on the presence of known TFBS in the promoters of differentially expressed genes, we found that HOXD10 is not induced by VEGFR-3 stimulation on the mRNA level, but is activated as early as 15 min after the stimulus. The mechanism by which activated VEGFR-3 triggers HOXD10 activity is entirely unknown, but it has been reported that the transcription factors of the HOX cluster 10, to which HOXD10 belongs, contain several putative tyrosine phosphorylation sites in the homeodomain flanking regions (Guerreiro et al, 2012). Thus, the trigger of HOXD10 activity downstream of VEGFR-3 stimulation might well be a phosphorylation event.…”
Section: Discussionmentioning
confidence: 99%
“…A similar tag was also present in Pax3 (Guerreiro et al, 2013). Deletion and swapping mutants were produced using a PCR-based mutagenesis strategy (Guerreiro et al, 2012) and their sequences verified.…”
Section: Mutant Constructs and Transgenic Micementioning
confidence: 99%
“…Electrophoretic mobility shift assays were performed as previously described (Guerreiro et al, 2012) using proteins produced in 293T cells. The DNA probe corresponding to the H1 enhancer has been described previously (Guerreiro et al, 2012).…”
Section: Phenotypic and Biochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation